1998
DOI: 10.1002/rem.3440080306
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical and Hydrologic Monitoring of Air Sparging Flow Behavior: Comparison of Two Extreme Sites

Abstract: As a groundwater cleanup technology, air sparging has been shown to be an effective alternative to pump and treat when systems are correctly designed and subsurface conditions are favorable (Bass and Brown, 1995).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…They reported that air flow was confined to a zone with a 0.3-to 0.6-m radius in homogenous formations. Similar patterns were reported by Lundegard and LaBrecque (1998), who used an electrical resistance tomography system to map air distributions, and McKay and Acomb (1996), who mapped air distributions with neutron logs. In both cases, steady-state air distribution was centered on the injection point with the bulk of the flow occurring within a 0.3-to 1-m radius.…”
Section: Soil Texturesupporting
confidence: 75%
“…They reported that air flow was confined to a zone with a 0.3-to 0.6-m radius in homogenous formations. Similar patterns were reported by Lundegard and LaBrecque (1998), who used an electrical resistance tomography system to map air distributions, and McKay and Acomb (1996), who mapped air distributions with neutron logs. In both cases, steady-state air distribution was centered on the injection point with the bulk of the flow occurring within a 0.3-to 1-m radius.…”
Section: Soil Texturesupporting
confidence: 75%
“…This is particularly the case when site data suggest that one or more layers may be present in the subsurface that control air distribution. The use of neutron probes, capacitance probes, and electrical resistance tomography to identify aeration zones have all been reported in the literature (e.g., Acomb et al, 1995;Lundegard and LaBreque, 1998). These techniques generally have the ability to detect the presence of air in the subsurface at the "10% by volume" level.…”
Section: Sf 6 Distribution Test (Pt7)mentioning
confidence: 99%